Bitter Cinema. On Occupation in 26 Pictures by Lordan Zafranović - Hendrykowski, Marek (Poznańskie Studia Slawistyczne, 2017)
Analysis and interpretation of the film fresque made by Croatian director Lordan Zafranović (1978), a masterpiece of European art cinema of 70s. Marek Hendrykowski’s study describes relationship between poetics of experience and aesthetics of shock. It also expresses the importance of mythical perspective (Babel Tower) and its meaning as the factor of common consciousness in keeping memory of the past in art and life of contemporary societies.